2012
DOI: 10.5152/akd.2012.008
|View full text |Cite
|
Sign up to set email alerts
|

Association between C-reactive protein, carotid intima-media thickness and P-wave dispersion in obese premenopausal women: an observational study

Abstract: Association between C-reactive protein, carotid intima-media thickness and P-wave dispersion in obese premenopausal women: an observational studyPremenapozal şişman kadınlarda P dalga dispersiyonu karotis intima-media kalınlığı ve C-reaktif protein arasındaki ilişki; Gözlemsel bir çalışma Original Investigation Özgün Araşt›rma ABSTRACTObjective: The aim of the present study was to evaluate P-wave dispersion (PWD) in obese women, and to investigate the relationship between P-wave measurements, high sensitive C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…CIMT is an indicator of atherosclerosis, and studies have shown that it is an indicator of cardiovascular events and mortality (912). It has also been found to be associated with CAD, coronary atherosclerotic load, endothelial dysfunction, and mitral annular calcification, which has a value in the prediction of atherosclerosis and arrhythmias (1319). …”
Section: Introductionmentioning
confidence: 99%
“…CIMT is an indicator of atherosclerosis, and studies have shown that it is an indicator of cardiovascular events and mortality (912). It has also been found to be associated with CAD, coronary atherosclerotic load, endothelial dysfunction, and mitral annular calcification, which has a value in the prediction of atherosclerosis and arrhythmias (1319). …”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that interatrial conduction delays are associated with initiating and maintaining atrial fibrillation [35,36]. Furthermore, some authors reported increased PWD is associated with stable coronary artery disease, carotid atherosclerosis, and slow coronary phenomenon [9,37,38]. This suggests that another pathophysiological mechanism for increased PWD is endothelial dysfunction as well as autonomic imbalance.…”
Section: Discussionmentioning
confidence: 99%
“…PD has also been found to be associated with carotid atherosclerosis [8]. In addition, it has been shown that P-wave dispersion is increased in coronary slow- flow phenomenon [25].…”
Section: Discussionmentioning
confidence: 99%
“…A growing evidence shows that people who are higher PD have higher risks for several cardiovascular-related conditions such as diabetes mellitus, obesity, hypertension, peripheral vascular disease, and myocardial infarction [4-7]. Furthermore, PD has been found to be to associated with an increase in carotid intima-media thickness and inflammatory markers such as C-reactive protein [8]. However, there are very few studies that have shown the relationship between stable coronary artery disease and P wave dispersion [9].…”
mentioning
confidence: 99%